دور الدائن والمدين في عملية تسوية الالتزامات المالية للمدين في ظل قانون إعسار المدين رقم 19 لسنة 2019 - ماليه، بيير (جامعة الإمارات العربية المتحدة - كلية القانون, 2021)
The UAE Cabinet approved a federal law to regulate cases of insolvency of natural persons or individuals. In 2016, the UAE government had adopted a similar insolvency law for companies which was widely welcomed by businesses and financial institutions. The legal framework for insolvency for both companies and individuals are expected to improve the competitiveness and the ease of doing business of the UAE. Debt restructuring for individuals under legal protection is widely seen as a great step forward in helping those who are unable to pay their debts from going bankrupt. “The approval of a new federal law to regulate the cases of personal insolvency is a step forward in improving the ease of doing business for both debtors and creditors. A legal framework for addressing debts and financial difficulties will help them reschedule their debts and provide them with the opportunity to be granted new concessional loans. “The introduction of any form of personal insolvency regime is a critical step in both enhancing and rounding out the already improved UAE insolvency provisions. In this article we will present the role of the civil debtor and the creditor in the period of debt restructuring. We will start with the role of the debtor as soon as debt restructuring is requested, then its role during the preparation of the debt restructuring, then its role in the execution of the plan and finally its role with the end of the plan. In the second part we will examine the role of the creditor in the preparation of the debt restructuring plan then its role in the execution of the plan finally we will study its role in the end of the plan. We will present in our conclusion the results of our research and the recommendations.
وافق مجلس الوزراء الإماراتي على قانون اتحادي لتنظيم حالات إعسار الأشخاص الطبيعيين، أو الأفراد في عام ٢٠١٦، اعتمدت حكومة الإمارات العربية المتحدة قانون إعسار مماثل للشركات، وقد حظي بالترحيب على نطاق واسع من قبل الشركات، والمؤسسات المالية. من المتوقع أن يعمل الإطار القانوني للإفلاس لكل من الشركات، والأفراد على تحسين القدرة التنافسية، وسهولة ممارسة الأعمال التجارية في الإمارات العربية المتحدة. ينظر إلى إعادة هيكلة الديون لغير التجار على أنها خطوة كبيرة إلى الأمام في مساعدة أولئك الذين لا يستطيعون سداد ديونهم من الإعسار. تعد الموافقة على قانون اتحادي جديد لتنظيم حالات الإعسار الشخصي خطوة إلى الأمام في تحسين سهولة ممارسة الأعمال التجارية لكل من المدينين، والدائنين. وسيساعدهم هذا الإطار القانوني في معالجة الديون، والصعوبات المالية من خلال إعادة جدولة ديونهم، وتزويدهم بفرصة منح قروض جديدة. في هذا البحث سوف نشرح دور كل المدين المدني، والدائن في فترة إعادة هيكلة الديون. سنبدأ مع دور الدين بمجرد طلب إعادة هيكلة الديون، ثم دوره أثناء إعداد خطة إعادة هيكلة الديون، ودوره في تنفيذ الخطة، وأخيرا دوره مع نهاية الخطة. في الجزء الثاني سوف ندرس دور الدائن في إعداد خطة إعادة هيكلة الديون، ثم دوره في تنفيذ الخطة، وفي النهاية سوف ندرس دوره في نهاية الخطة. سوف نقدم في خاتمتنا نتائج بحثنا، وتوصياتنا.
Keywords: قانون إعسار المدين -- المقترضين -- إعادة هيكلة الديون -- الامارات